Results of Surgical Treatment of Unstable Distal and Radius Fractures with Articular Involvement in Adults - Serbest, Sancar; Kesgin, Engin; Tosun, Hacı Bayram; Gökçe, Halil; Bayram, Hüseyin (Fırat University, 2013)
Objective: Results of surgical treatment for unstable distal end radius fractures with articular involvement in adults as comparing with unlocked and locked anatomic plate by volar approach were evaluated. Materials and Methods: According to AO classification type C with 35 patient treated open reduction and two different volar plate fixation for distal end of the radius fractures retrospectively reviewed between January 2005 and May 2009. All type C fractures were evaluated 16 (% 46) C1, 9 (% 29) C 2, 10 (% 28) C3. The median follow-up period was 20 month (6-50). Volar locked plate treatment was used for 13 patient in Group 1 and volar unlocked anatomic plated was used 22 patient in Group 2. There were no statiscally differences in age, gender, fracture type among groups. Results: According to Gardland and Werley cilinically evaluation criters; excellent-good was % 86, fair was % 14 in group 1; excellent-good % 77, fair was % 23 in Group 2 respectively. Wrist range of motion and forearm rotation was similar statistically for 2 groups as were clinical scoring and grip strenght.According to radiological evaluation system of Steward et al. excellent-good were % 100; in Group 1 and % 91 in Group 2 respecti-vely. Althought there was no statistically differences among groups, but in locked plate group radiological improvement was better. Conclusion: Treatment of complex distal end fractures of radius involment articular with volar unlocked or locked plate provide good functional results and late period follow up there were no difference in terms of functional and radiologic results among two method. Locked anatomic plates provide good radiologic correction because of including multiple screws with low profile and allow to early joint movement because of rigidity.

Amaç: Eklemi ilgilendiren instabil radius distal uç kırıklarının cerrahi tedavisinde volar girişimle uyguladığımız kilitsiz ve kilitli anatomik plakla tespit yöntemlerinin sonuçları değerlendirmek. Gereç ve Yöntem: Çalışmamızda Ocak 2005 ile Mayıs 2009 arasında AO sınıflandırmasına göre C grubunda yer alan radius distal uç kırığı nedeniyle açık redüksiyon ve iki değişik volar plak tespitiyle tedavi edilen erişkin 35 distal radius kırıklı hasta retrospektif olarak değerlendirildi. Hepsi Tip C olan kırıkların alt grupları 16 (% 46)'sı C1, 9 (% 26)'u C2, 10 (% 28)'u C3 şeklindeydi. Ortalama takip süresi 20 ay (6-50 ay) idi. Grup 1'deki 13 hastaya volar kilitsiz plak, Grup 2'deki 22 hastaya volar anatomik kilitli plak uygulandı. Gruplar arasında yaş, cins ve kırık tipi yönünden istatistik olarak anlamlı bir fark yoktu. Bulgular: Gartland ve Werley klinik değerlendirme kriterlerine göre Grup 1'de % 86 mükemmel-iyi, % 14 orta sonuç; Grup 2'de % 77 mükemmel-iyi, % 23 orta sonuç alındı. Her iki grup için eklem hareket açıları kavrama güçleri ve klinik değerlendirme sonuçları arasında istatistik olarak fark yoktu. Stewart radyolojik değerlendirmesine göre mükemmel-iyi sonuç Grup 1'de % 100, Grup 2'de % 91 olarak bulundu. Gruplar arasında istatistik olarak fark yoktu, ancak kilitli anatomik plak yapılan grupta radyolojik düzelme daha iyiydi. Sonuç: Radius distal uç kırıklarının eklemi ilgilendiren kompleks kırıklarının kilitsiz veya kilitli anatomik volar plaklarla tedavisinden iyi fonksiyonel sonuçlar alınmış, geç dönemde iki yöntem arasında fonksiyonel ve radyolojik sonuçlar yönünden fark bulunamamıştır. Ancak, kilitli anatomik plaklar distalde çok sayıda ve düşük profilli vida içerdiği için daha iyi radyolojik düzelme sağlamakta ve sıkılıkları nedeniyle erken harekete izin vermektedir.
Erişkinlerde Eklemi İlgilendiren İnstabil Radius Distal Uç Kırıklarının Cerrahi Tedavi Sonuçları